2021
DOI: 10.3390/ani11040959
|View full text |Cite
|
Sign up to set email alerts
|

Use of Omics Data in Fracture Prediction; a Scoping and Systematic Review in Horses and Humans

Abstract: Despite many recent advances in imaging and epidemiological data analysis, musculoskeletal injuries continue to be a welfare issue in racehorses. Peptide biomarker studies have failed to consistently predict bone injury. Molecular profiling studies provide an opportunity to study equine musculoskeletal disease. A systematic review of the literature was performed using preferred reporting items for systematic reviews and meta-analyses protocols (PRISMA-P) guidelines to assess the use of miRNA profiling studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Another class of RNAs, microRNAs (miRNAs), bind to target mRNAs and regulate gene expression and are routinely profiled in many human diseases 43 . To date, three miRNA studies have profiled equine musculoskeletal disease (tendon injury, laminitis and osteochondrosis) but none were related to equine stress fractures (reviewed in 44,45 ).…”
Section: Transcriptomicsmentioning
confidence: 99%
“…Another class of RNAs, microRNAs (miRNAs), bind to target mRNAs and regulate gene expression and are routinely profiled in many human diseases 43 . To date, three miRNA studies have profiled equine musculoskeletal disease (tendon injury, laminitis and osteochondrosis) but none were related to equine stress fractures (reviewed in 44,45 ).…”
Section: Transcriptomicsmentioning
confidence: 99%
“…The study of DNA, RNA, protein and metabolites is referred to as genomics, transcriptomics, proteomics and metabolomics respectively. A recent scoping and systematic review of the literature 8 identified a genome association study with no transcriptomic, proteomic or metabolomic studies pertaining to fractures in racehorses confirming the gap in the scientific literature in this area. We anticipate that veterinary researchers will set out to fill this gap soon.…”
mentioning
confidence: 97%
“…Pre-analytical factors that can influence microRNA expression were identified as fasting, exercise and diet, for example, microR-NA-21 has been reported to increase with exercise in three publications. 8 Analytical factors that vary between studies are the platform used to quantify microRNA such as RNA-seq, RT-qPCR or miRNA arrays. Post-analytical factors that can influence results include how reference genes are selected for individual studies and the statistical approaches used to determine the false discovery rate in RNAseq analyses.…”
mentioning
confidence: 99%
See 2 more Smart Citations